STRATEGI MANAJEMEN PRODUKSI SENJATA JENIS XX PT. ABC DALAM MENANGGAPI PERMINTAAN YANG FLUKTUATIF - Maulana Arief Rachman Hakim (Aliansi : Jurnal Manajemen dan Bisnis, 2018)
Indonesia has limited budget to fulfill national defense posture, which cause unstable and fluctuation demand of main tool of weapon systems need. Industry in response to uncertain demand, requires good production planning for the ongoing business cycle. The research problem is how the ideal production strategy in response to fluctuating demand. Research question are analyzing user demand patterns, and production strategies, and ideal production management for industry in response to fluctuating demand. The research used qualitative method. The data obtained then analyzed by qualitative analysis techniques. The result show that user demand is based on availability of budget, which cause the user cannot provide certainly to the demand of main weapon system, the shortterm contract are complicate the industry to design their production plan. The Industry implements the MRP system, in its application, raw materials that are difficult to fulfill due to constrained policies and production machinery that often occur due to the old machine age becomes a problem in the application of MRP system, because MRP which will plan the production needs and the time required to stage of delivery. Implementation of the MRP should ideally be integrated with Just-In-Time and anticipated by the model of lowering risk with gradual change. Conclusions, marketing strategy has not been effective, so that it requires good coordination among relevant stakeholders, the fulfillment of production resources that also have limitations need to be anticipated with an effective production strategy, so that the production strategy is able to adjust the conditions that cannot be ensured, Strategy with the application of MRP system combined with Just-In-Time and method of lowering risk with gradual change, it is expected that the industry can survive the fluctuating demand and the policy that makes the limitations.